2006
DOI: 10.5210/fm.v11i11.1413
|View full text |Cite
|
Sign up to set email alerts
|

An empirical examination of Wikipedia's credibility

Abstract: Wikipedia is an free, online encyclopaedia which anyone can add content to or edit the existing content of. The idea behind Wikipedia is that members of the general public can add their own personal knowledge, anonymously if they wish. Wikipedia then evolves over time into a comprehensive knowledge base on all things. Its popularity has never been questioned, although its authority has. By its own admission, Wikipedia contains errors. A number of people have tested Wikipedia’s accuracy using destructive method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(156 citation statements)
references
References 0 publications
2
139
1
5
Order By: Relevance
“…One way this issue has been approached is by empirically comparing content in Wikipedia with other encyclopaedias or with what are regarded as external facts (eg. Chesney, 2005;Giles, 2005;Holman Rector, 2007). Another way of approaching the trustworthiness of Wikipedia is from an epistemological perspective, taken from philosophy.…”
Section: Research In Wikipedia and Wikipedia Editorsmentioning
confidence: 99%
“…One way this issue has been approached is by empirically comparing content in Wikipedia with other encyclopaedias or with what are regarded as external facts (eg. Chesney, 2005;Giles, 2005;Holman Rector, 2007). Another way of approaching the trustworthiness of Wikipedia is from an epistemological perspective, taken from philosophy.…”
Section: Research In Wikipedia and Wikipedia Editorsmentioning
confidence: 99%
“…Although research to date has not focused on the credibility of Wikipedia for political information specifically, studies have shown that user-created entries in Wikipedia are about as accurate as well-regarded print encyclopedias such as Encyclopaedia Britannica (Andrews, 2007;Giles, 2005;Williams, 2008), and entries from Wikipedia have been evaluated as credible, particularly by area experts (Chesney, 2006). This is true despite Internet users' concerns about the credibility of the information found there (Metzger, Flanagin, and Medders, 2010;Nofrina et al, 2009), which may be driving results of studies showing that people perceive the same information to be less credible if they think it comes from Wikipedia than if they think it comes from Encyclopaedia Britannica Kubiszewski, Noordewier, and Costanza, 2011).…”
Section: Wikipediamentioning
confidence: 99%
“…Actually, the quality of Wikipedia was compared and found close to that of Encyclopedia Britannica [5]. However, another study showed that Wikipedia was not a totally reliable resource [6]. Nevertheless, even Wikipedia itself claimed that "Wikipedia may not be ideal as a source for all academic uses, and (as with other sources) suggests that at the least, one strength of Wikipedia is that it provides a good starting point for current information on a very wide range of topics."…”
Section: B Using Wikipedia In Educationmentioning
confidence: 99%